2020
DOI: 10.1039/c9ra09893c
|View full text |Cite|
|
Sign up to set email alerts
|

Research into the thermal stability and mechanical properties of vitamin E diffusion modified irradiation cross-linked graphene oxide/ultra-high molecular weight polyethylene composites

Abstract: Recently, there has been increasing interest in modifying ultra-high molecular weight polyethylene (UHMWPE) due to glaring needs in the artificial joint replacement field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 41 publications
(78 reference statements)
1
25
0
Order By: Relevance
“…It ascribes to the fact that r‐GO in extracted fibers can work as crystallization core, which can greatly increase the grain size and crystallization rate for extracted fibers. This result was well supported by the DSC analysis and the results of reported literature 63 …”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…It ascribes to the fact that r‐GO in extracted fibers can work as crystallization core, which can greatly increase the grain size and crystallization rate for extracted fibers. This result was well supported by the DSC analysis and the results of reported literature 63 …”
Section: Resultssupporting
confidence: 90%
“…This result was well supported by the DSC analysis and the results of reported literature. 63 Compared with corresponding extracted fibers, the G (110) and G (200) of drawn fibers decreases due to grain refinement in hot drawing process. 34,61,64 Meanwhile, the grain sizes of modified UHMWPE fiber increase with increasing concentration of m-GO.…”
Section: Crystallinity and Crystal Size Of Uhmwpe Fibersmentioning
confidence: 96%
“…If there is a chemical change (such as a change in the crystalline structure of the material) after the sterilization processes and which may affect the material's stability, it is possible to verify these changes by analyzing the resistance of the sample to forced oxidation. TGA is a suitable characterization of oxidative stability in UHMWPE, 51 being widely used in recent studies, 52,53 serving here as a way to compare the sterilization processes with pristine conditions in terms of their thermal stability. According to the results presented in Fig.…”
Section: Thermal Analysismentioning
confidence: 99%
“…Duan 7 fabricated graphene oxide (GO)/UHMWPE composites by means of liquid ultrasonic dispersion, hot pressing and irradiation cross‐linking, followed by VE diffusion and homogenization treatment. The results indicated that irradiation cross‐linking and limited VE diffusion can improve the performances of UHMWPE substrate.…”
Section: Introductionmentioning
confidence: 99%